A bibliometric analysis on the progress of myocardial bridge from 1980 to 2022 - Chen, Liang; Yu, Wen-Yuan; Liu, Rui; Gao, Ming-Xin; Wang, Bo-Lin; Ding, Xiao-Hang; Yu, Yang (Frontiers in Cardiovascular Medicine, 2023)
Introduction Although the vast majority of patients with a myocardial bridge (MB) are asymptomatic, the anomaly was found to be associated with stable or unstable angina, vasospastic angina, acute coronary syndrome, and even malignant arrhythmias and sudden cardiac death in some cases. Methods By retrieving the relevant literature on MB from 1 January 1980 to 31 July 2022 from the Web of Science Core Collection (WoSCC) database, we used the bibliometric tools, including CiteSpace, VOS viewer, and alluvial generator, to visualize the scientific achievements on MB. Results A total of 630 articles were included. The number of published articles was in a fluctuating growth trend. These publications came from 37 contries, led by the USA and China. The leading country on MB was the United States, the leading position among institutions was Stanford University, and the most productive researcher on MB was Jennifer A. Tremmel. After analysis, the most common keywords were myocardial bridge, mortality, coronary angiography, descending coronary artery, and sudden death. Conclusion Our findings can aid researchers in understanding the current state of MB research and in choosing fresh lines of inquiry for forthcoming investigations. Prevalence and prognosis, mechanism atherosclerosis, hemodynamic significance, and molecular autops will likely become the focus of future research. In addition, more studies and cooperations are still needed worldwide.